2016
DOI: 10.1002/2015wr017587
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sensible heat flux estimation over heterogeneous surfaces using multitemporal land‐surface temperature observations

Abstract: Equations based on surface renewal (SR) analysis to estimate the sensible heat flux (H) require as input the mean ramp amplitude and period observed in the ramp-like pattern of the air temperature measured at high frequency. A SR-based method to estimate sensible heat flux (H SR-LST ) requiring only lowfrequency measurements of the air temperature, horizontal mean wind speed, and land-surface temperature as input was derived and tested under unstable conditions over a heterogeneous canopy (olive grove). H SR-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Other measurements are based on scintillometry, lisimetry, and surface renewal (e.g., [12][13][14]). …”
Section: Methodsmentioning
confidence: 99%
“…Other measurements are based on scintillometry, lisimetry, and surface renewal (e.g., [12][13][14]). …”
Section: Methodsmentioning
confidence: 99%
“…Approaching the shear at the canopy top by u*/hc (hc is the canopy height), the semi-empirical Equation ( 6) was proven reliable for a variety of canopies. Assuming that the maximum temperature to be reached by the parcel of air is LST, Equation (7) proposes a linear relationship between quantities (LST-T) and A where T is the potential temperature of the air measured at a reference height above the canopy [21,22]. In Equation (7), b is a coefficient (hereafter referred to as offset) that corrects for the fact that (LST-T) may not necessarily follow the adiabatic lapse rate at neutral conditions (i.e., case where A = 0 K) and z0m is the roughness length for momentum.…”
Section: Sensible Heat Fluxmentioning
confidence: 99%
“…Thus, ε0 was set to 0.97. The offset in Equation ( 7) was determined as in Castellví et al(2016) [22]. Thus, the coefficient b at sunrise and sunset was determined setting A = 0 K, at noon the offset was set to zero and for the rest of the day it was calculated using a linear relationship from sunrise to noon and from noon to sunset.…”
Section: Solving the Sensible And Latent Heat Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of surface turbulent structures with surface temperature fluctuations has been draw attention gradually. The turbulent structures sweep the interface and give rise to surface temperature fluctuations [16] [17]. Recent studies have revealed that the characteristic of the near-surface airflow can be indirectly deduced based on surface high frequency temperature fluctuations.…”
Section: Introductionmentioning
confidence: 99%